Adolescent sexuality in a cross-cultural perspective - Landripet, Ivan (2001)
The presentation deals with the main attitudinal and behavioral aspects of adolescent sexuality in contemporary Europe. An overview of the findings from studies published in various European countries is provided.
ENG